A direct simple shear device for static liquefaction triggering under constant shear drained loading. Issue 2 (18th June 2019) - Reid, D.; Fourie, A.
Abstract : The development of a direct simple shear device to carry out constant shear drained (CSD) tests is outlined. The purpose of the device is to study static liquefaction instability triggered by a rising phreatic surface under principal stress directions representative of conditions below a slope. A series of tests on a laboratory-standard sand are outlined, indicating ( a ) brittle instability under a drained increasing phreatic surface, ( b ) a reasonable trend between the instability stress conditions and the sample density and ( c ) a general agreement between the qualitative behaviour seen in the new device and the previous CSD testing carried out on saturated samples under dead weight. The sensitivity of the instability stress conditions to sample density is emphasised.